Patent Activity in Biotechnology - Ekaterina Streltsova (Foresight and STI Governance, 2014)
Biotechnologies are a priority area of development due to the scope of global challenges and social problems they help to resolve. There is demand for updated information about the the current state of research and challenges faced. This paper discusses the potential of patent analysis and surveys the Russian biotechnological market with both quantitative and qualitative methods. It reviews key statistical and analytical findings of empirical research.